1999
DOI: 10.1042/cs19990162
|View full text |Cite
|
Sign up to set email alerts
|

Comparable vasorelaxant effects of 17α- and 17β-oestradiol on rat mesenteric resistance arteries: an action independent of the oestrogen receptor

Abstract: 17beta-Oestradiol (17betaE(2)) has vasorelaxant properties that may contribute to its beneficial cardiovascular effects. The mechanism of vasorelaxation remains controversial, but does not appear to involve interaction of 17betaE(2) with its nuclear receptor. The present study examined the effects on resistance arteries of 17betaE(2) and its isomer, 17alpha-oestradiol (17alphaE(2)), which does not bind to the classical oestrogen receptor. In arteries precontracted with either noradrenaline or KCl, 17betaE(2) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
8
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 38 publications
3
8
0
Order By: Relevance
“…This reduced sensitivity to E 2 in larger arteries is in agreement with findings of others (Lindsey et al 2011). Furthermore, the differential sensitivities to E 2 of the mesenteric, renal, and uterine arteries observed in this study are similar to values reported by others (Naderali et al 1999, Leung et al 2005, Scott et al 2007 Previous studies have shown that in vivo administration of the nonselective ER antagonist ICI 182 780 into one uterine artery of ovariectomized and E 2 -treated nonpregnant sheep blunted the E 2 effect on uterine blood flow, confirming its ER dependence (Magness et al 2005). Here, we show that ICI 182 780 resulted in a significant rightward shift in the CRCs to E 4 and E 2 , suggesting the contribution of ER.…”
Section: Discussionsupporting
confidence: 83%
“…This reduced sensitivity to E 2 in larger arteries is in agreement with findings of others (Lindsey et al 2011). Furthermore, the differential sensitivities to E 2 of the mesenteric, renal, and uterine arteries observed in this study are similar to values reported by others (Naderali et al 1999, Leung et al 2005, Scott et al 2007 Previous studies have shown that in vivo administration of the nonselective ER antagonist ICI 182 780 into one uterine artery of ovariectomized and E 2 -treated nonpregnant sheep blunted the E 2 effect on uterine blood flow, confirming its ER dependence (Magness et al 2005). Here, we show that ICI 182 780 resulted in a significant rightward shift in the CRCs to E 4 and E 2 , suggesting the contribution of ER.…”
Section: Discussionsupporting
confidence: 83%
“…To exclude possible vascular effects of ethanol, two arteries from each animal in each experiment were studied in the presence of the same volume of ethanol as the test arteries. As reported previously, there was no significant effect of this low concentration of ethanol on contractility induced by either KPSS or NA [29,30].…”
Section: Reagentssupporting
confidence: 70%
“…literature. Indeed, some laboratories have reported that 17␣-E 2 relaxed pig coronary arteries without achieving complete dilatation when contracted with Ca 2ϩ (34), while others noted that 17␣-E 2 generated relaxation similar to that of 17␤-E 2 in the mesenteric arteries of rats (26). On the other hand, 17␣-E 2 displayed only minor effects on mesenteric artery diameter over a concentration range similar to the effective vasodilatory concentration of 17␤-E 2 in the same strain of rats (37).…”
Section: Discussionmentioning
confidence: 90%